الفكر الأصولي عند الإمام الشافعي : دراسة تحليلية نقدية - Shaib Mohd Wani
This Research aims to study the Usuli thought of Imam al-Shafi'i as a comprehensive legal methodology. The researcher begins with an inductive study of the works of Imam al-Shafi'i, his companions and students, which led to the elucidation of the Usuli project of al-Shafi'i, its foundations and the reasons behind its codification. And it became clear that its main aim was reconciliation between the methods of Ahl al-Ra’y and Ahl al-Hadith which was the main cause of methodological inconsistency in understanding the texts of Qur’an and Sunnah. The researcher further explained the main foundation of the Usuli thought of Imam al-Shafi'i : al-Bayan, a subtle Qur’an-Sunnah interaction which produces all law. And the main tool of understanding this interaction is the Arabic language. This innovative principle: al-Bayan is the genius of al-Shafi'i. After that, the researcher discusses the types of al-Bayan: By Qur'an, Sunnah and Ijtihad. The researcher also explains some of the most important issues connected with these types. In conclusion, by his legal thought, Imam al-Shafi'i laid foundation of a logical and consistent methodology of law which is a balance between the Ahl al-Ra’y and Ahl al-Hadith approaches.